Evaluation and performance analysis of Chinese remainder theorem and its application to lossless image compression - Vidhya, R.; Brindha, M. (Journal of ambient intelligence and humanized computing, 2023)
Chinese remainder theorem (CRT) is widely utilized in many cryptographic applications and additionally the reversible nature of CRT is employed in compression of images. This paper mainly focuses on the suitability of CRT for lossless image compression and the analysis is carried out for the number and range of primes to be chosen. With respect to the analysis is carried out for the number of primes to be chosen (i.e., 2, 3, 4, 5, and 6), it is found that CRT suits well only for the chosen number of primes 2 with good compression ratio. For the remaining prime numbers, it provides negligible or even negative CR based on the chosen number of prime numbers. Also, CRT based lossless compression (CRTLC) reduces the size of the image based on the number of primes chosen. Further, it can achieve substantial compression of the original image. Using different test images, CRT is compared with recent lossless compression methods and against the standard set of lossless compression techniques (i.e., JPEG 2000, JPEG-LS, and CALIC). From these comparisons, it is inferred that CRT scores (maximum achieved CR is 1.8823) better than the recent and standard algorithms.